Preparation method and application of superfine iron-molybdenum catalyst
By adding complexing agent and nitric acid during the preparation of iron-molybdenum catalyst, the ultrafine iron-molybdenum catalyst was prepared, which solved the problems of catalyst sintering and Mo segregation at high temperatures, improved the activity and life of the catalyst, and improved the selectivity of methanol Efficiency of oxidation to prepare formaldehyde.
Patent Information
- Application Number
- CN202411606144.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-01-10
AI Technical Summary
Iron-molybdenum catalysts are prone to sintering and Mo group isolation under high temperature conditions, resulting in a decrease in catalyst activity and lifetime. The iron-rich sites exposed after Mo loss have low selectivity for formaldehyde, resulting in excessive oxidation of methanol to produce CO and CO2. , the catalyst life is short.
By adding complexing agent and nitric acid to the water-soluble iron salt solution, the formation of polyferrous ions and iron hydroxide is reduced, and ultrafine iron-molybdenum catalyst is prepared by impregnation method or co-precipitation method to enhance the dispersion of Fe and Mo components. , reduce the particle size distribution range and improve the activity and life of the catalyst.
The high-temperature stability and activity of the catalyst are improved, the service life of the catalyst is extended, the selectivity and conversion rate of formaldehyde prepared by selective oxidation of methanol is improved, and the isolation of Mo components at high temperature is reduced, which is of commercial application value.
Smart Images

Figure CN119281346A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nano material synthesis, and specifically relates to a method for preparing an ultrafine iron-molybdenum catalyst, and application of the prepared ultrafine iron-molybdenum catalyst in catalyzing the selective oxidation of methanol to prepare formaldehyde. Background Art
[0002] Formaldehyde is an important intermediate in the chemical industry. At present, the production of formaldehyde by methanol catalytic oxidation mainly includes the silver process and the iron-molybdenum process. The iron-molybdenum process is gradually replacing the silver process due to its high formaldehyde yield and low reaction temperature. However, the active component Mo in the iron-molybdenum catalyst has a low melting point and is easily separated at high temperatures, changing the catalyst structure and reducing the reaction activity; in addition, the iron-rich sites exposed after the loss of Mo have low selectivity for formaldehyde, and methanol is easily over-oxidized to produce CO and CO2, which is the reason for the short life of the iron-molybdenum catalyst (about 0.5 to 1 year); in addition, the lost Mo will be deposited in the gaps between the catalyst particles in the form of needle-like crystals, which will increase the pressure drop of the reactor and is not conducive to production. In industrial applications, the Mo / Fe molar ratio of the iron-molybdenum catalyst is usually higher than the stoichiometric ratio of iron molybdate to compensate for the loss of Mo during the reaction.
[0003] Iron-molybdenum catalysts undergo sintering and segregation under high temperature conditions, which affects the activity and life of the catalyst. In order to optimize the thermal conductivity and high temperature control of iron-molybdenum catalysts, it is necessary to start with catalyst synthesis, improve the dispersion of Fe and Mo components, reduce catalyst particle size distribution and morphology, and other factors to improve the catalytic activity of the catalyst and reduce the degree of segregation of the Mo component at high temperature. Summary of the invention
[0004] In order to solve the problem of decreased catalyst activity and life due to sintering and Mo component separation of iron-molybdenum catalysts under high temperature conditions, the present invention provides a method for preparing an ultrafine iron-molybdenum catalyst, which reduces the particle size of the iron-molybdenum catalyst and enhances the dispersion of Fe and Mo components, thereby reducing the precipitation of Mo from the main phase and improving the activity and life of the catalyst.
[0005] The preparation method of the ultrafine iron-molybdenum catalyst provided by the present invention comprises the following steps:
[0006] Step 1: Add a complexing agent to an aqueous solution of a trivalent iron salt, and then add an aqueous solution of nitric acid to change the solution from a reddish brown opaque state to a clear state, and stir for 1 to 4 hours to obtain a mother solution.
[0007] Step 2: Using an impregnation method, the mother liquid of step 1 is impregnated into MoO3 powder, and then calcined to obtain an ultrafine iron-molybdenum catalyst; or using a coprecipitation method, the mother liquid of step 1 is coprecipitated with ammonium molybdate and then calcined to obtain an ultrafine iron-molybdenum catalyst. The molybdenum-iron atomic ratio in the iron-molybdenum catalyst is 1:1 to 3:1.
[0008] In the above step 1, the complexing agent is any one of high molecular polymers such as polyethylene glycol, polyvinyl alcohol, polyvinyl pyrrolidone, etc., and the added mass of the complexing agent is preferably Fe in trivalent iron salt. 3+ 0.5 to 3 times the mass.
[0009] In the above step 1, the trivalent iron salt is ferric nitrate or ferric chloride.
[0010] In the above step 1, the concentration of the nitric acid aqueous solution is 1 to 8 mol / L.
[0011] Furthermore, in the above step 2, the MoO3 powder is added to the mother liquor of step 1 by impregnation method, stirred for 2 to 6 hours to completely evaporate the water, dried at 80 to 120°C, and calcined at 400 to 500°C for 4 to 16 hours to obtain an ultrafine iron-molybdenum catalyst.
[0012] Furthermore, in the above step 2, a co-precipitation method is adopted, and an aqueous ammonium molybdate solution is added to the mother liquor of step 1, or the aqueous ammonium molybdate solution and the mother liquor of step 1 are added to a precipitation kettle at the same time, and the pH of the system is controlled at 1.7-2.4 by dropping ammonia water, and the iron-molybdenum powder obtained after co-precipitation is calcined at 400-500° C. for 4-16 hours to obtain an ultrafine iron-molybdenum catalyst.
[0013] The present invention also provides the use of the ultrafine iron-molybdenum catalyst in catalyzing the selective oxidation of methanol to prepare formaldehyde. The specific method is: the ultrafine iron-molybdenum catalyst powder is pressed into tablets and then loaded into a fixed bed reactor. The reactor inlet air velocity is 6000-13000h -1 The oxygen content in the inlet air is diluted with nitrogen to a volume concentration of 10% to 20%, and the pump speed is adjusted so that the volume fraction of methanol in the gas phase after gasification is 6% to 10%. The reaction is carried out under normal pressure and the reaction temperature is 280 to 350°C.
[0014] The beneficial effects of the present invention are as follows:
[0015] 1. The present invention adds a complexing agent and nitric acid to a water-soluble iron salt solution to make Fe 3+ The ions are complexed with the complexing agent under strong acidic conditions to reduce the formation of polyferric ions and ferric hydroxide in the solution system. In the process of preparing the catalyst by impregnation method, precipitation method, etc., Fe in the mother liquor is 3+ The dispersion is more uniform, thereby reducing the particle size of the iron-molybdenum powder, narrowing the particle size distribution range of the iron-molybdenum catalyst, and enhancing the dispersion of the Fe and Mo components, thereby reducing the precipitation of Mo from the main phase and improving the activity and life of the catalyst.
[0016] 2. The preparation method of the present invention is simple and low in cost. The obtained ultrafine iron-molybdenum catalyst is used to catalyze the selective oxidation of methanol to prepare formaldehyde with high selectivity and conversion rate. Benefiting from the uniform dispersion and narrow particle size distribution of iron and molybdenum components in the iron-molybdenum catalyst powder, the catalyst has high molding strength and good thermal stability, which reduces the precipitation of molybdenum components at high temperatures, thereby extending the service life and having commercial application and promotion value. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is the particle size distribution diagram of the catalyst powder obtained in Example 1. DETAILED DESCRIPTION
[0018] The present invention is described in detail below with reference to the accompanying drawings and examples, but the embodiments of the present invention are not limited thereto. Obviously, the embodiments described below are only partial embodiments of the present invention. For those skilled in the art, other similar embodiments obtained without creative labor all fall within the protection scope of the present invention.
[0019] In the examples, the catalyst was evaluated using a fixed bed device by selective oxidation of methanol to formaldehyde, and the particle size distribution of the catalyst and the content of Mo component before and after the reaction were tested using a laser particle size analyzer and an inductively coupled plasma emission spectrometer.
[0020] Example 1
[0021] 1. Preparation of FeMo catalyst
[0022] Step 1: Add 56 g of PEG-2000 to 0.5 L of 1 mol / L ferric nitrate nonahydrate aqueous solution; then add 70 mL of 1 mol / L nitric acid aqueous solution to change the solution from a reddish brown opaque state to a clear state, and stir for 1 hour to obtain a mother solution.
[0023] Step 2: Take 500g of molybdenum trioxide powder with an average particle size of 10μm, add it to the mother liquor of step 1 while stirring until the powder is completely soaked; after stirring for 4h, dry it at 120℃, and calcine it at 450℃ for 10h to obtain an ultrafine iron-molybdenum catalyst, recorded as FeMo-PEG-2000.
[0024] The particle size distribution of the calcined catalyst in Example 1 was measured using a laser particle size analyzer and compared with the FeMo catalyst (molybdenum-iron atomic ratio 2.5:1, denoted as FeMo-1) prepared by the traditional impregnation method (without adding PEG-2000 and nitric acid aqueous solution) and the FeMo catalyst prepared by the method of Example 1 above with only PEG-2000 added but without adding nitric acid aqueous solution (denoted as FeMo-2). The results are shown in Table 1.
[0025] Table 1 Catalyst particle size distribution
[0026] catalyst D10(μm) D25(μm) D50(μm) D90(μm) FeMo-1 0.773 8.420 15.888 41.965 FeMo-2 0.581 6.764 10.588 33.385 FeMo-PEG-2000 0.600 1.324 3.538 17.942
[0027] As can be seen from Table 1, the FeMo-1 catalyst prepared by the traditional impregnation method has a wide range of catalyst particle size after calcination, ranging from 0.8 to 42.0 μm, and D50 is 15.9 μm; the molybdenum trioxide powder is impregnated with the iron salt mother liquor after PEG-2000 complexation, and the particle size distribution range of the obtained catalyst FeMo-2 is reduced to 0.6 to 33.4 μm, and D50 is reduced to 10.6 μm; after the molybdenum trioxide powder is impregnated with the iron salt mother liquor after PEG-2000 complexation and nitric acid is added to adjust the degree of complexation, the particle size distribution range of the obtained catalyst FeMo-PEG-2000 is reduced to 0.6 to 17.9 μm, and D50 is reduced to 3.5 μm, as shown in Table 1. Figure 1 It can be seen that adding the complexing agent PEG-2000 to the ferric nitrate solution can reduce the particle size distribution range of the obtained catalyst and reduce its particle size, and nitric acid can adjust the Fe 3+ The degree of complexation with PEG increases Fe 3+ The dispersion degree can be improved, thus obtaining a narrower particle size distribution range and a smaller particle size.
[0028] 2. Selective oxidation of methanol to formaldehyde
[0029] On a fixed bed device, the catalyst prepared in Example 1 and the catalyst prepared by the above-mentioned traditional impregnation method were evaluated for their catalytic performance in the oxidation of methanol to formaldehyde according to the reaction conditions in Table 2. The specific method is as follows: the above-mentioned catalyst was dried to a water content of 15%, and 100-120 mesh powder was taken after grinding, and 2% of the catalyst mass of silica sol was added as a binder, and 2% of the catalyst mass of stearic acid was added as a lubricant. After fully mixing, the solid powder granulator was used to press into blocks at a pressure of 15MPa, and 40-60 mesh particles were taken after crushing, and sent to a tablet press to obtain Raschig ring-type catalyst tablets with a strength of >200N at a pressure of 10MPa. Then 5mL of Raschig ring-type catalyst tablets were taken and mixed evenly with 5mL of inert porcelain rings of the same size, and then filled into a fixed bed reactor. The reactor inlet air velocity was 10000h -1 The oxygen content in the inlet gas was diluted with nitrogen to a volume concentration of 10%. The pump speed was adjusted to make the volume fraction of methanol in the gas phase 8.4% after gasification. The reaction was carried out at normal pressure and the reaction temperature was 320°C. After the gas after the reaction was absorbed by water, the methanol content in the liquid sample was determined by gas chromatography, and the formaldehyde content in the liquid phase was titrated by sodium sulfite-sulfuric acid titration. The initial activity and selectivity of the catalyst are shown in Table 2. The loss of Mo components after long-term operation was also evaluated. The Mo content in the upper catalyst of the reactor before and after 720h of reaction (ICP test) is shown in Table 3.
[0030] Table 2 Catalyst reaction evaluation
[0031]
[0032] Table 3 Catalyst element content before and after reaction
[0033]
[0034]
[0035] As shown in Tables 2 and 3, the FeMo-PEG-2000 catalyst prepared in Example 1 can still maintain its initial activity and selectivity after 720 hours of reaction, and ICP confirms that the Mo content is not lost during the reaction.
[0036] Example 2
[0037] 1. Preparation of FeMo catalyst
[0038] Step 1: Add 30 g of PEG-6000 to 0.5 L of 1 mol / L ferric nitrate nonahydrate aqueous solution, and then add 200 mL of 1 mol / L nitric acid aqueous solution to change the solution from a reddish brown opaque state to a clear state, and stir for 1 h to obtain a mother solution.
[0039] Step 2: Add the mother liquor obtained in step 1 and 0.5L 0.5mol / L ammonium molybdate aqueous solution into a precipitation kettle, stir and react at 50°C for 4h, and add 10% ammonia water during stirring to control the pH of the system to be maintained at 2.2; after the reaction, filter and wash with deionized water, dry at 120°C, and calcine at 450°C for 10h to obtain an ultrafine iron-molybdenum catalyst, recorded as FeMo-PEG-6000.
[0040] The particle size distribution of the catalyst prepared in Example 2 was measured using a laser particle size analyzer and compared with the FeMo catalyst (molybdenum-iron atomic ratio 2.0:1, denoted as FeMo-3) prepared by the traditional coprecipitation method (without adding PEG-6000). The results are shown in Table 4.
[0041] Table 4 Catalyst particle size distribution
[0042] catalyst D10(μm) D25(μm) D50(μm) D90(μm) FeMo-3 0.715 7.365 15.390 44.075 FeMo-PEG-6000 0.498 1.001 2.552 14.942
[0043] 2. Selective oxidation of methanol to formaldehyde
[0044] In a fixed bed device, the catalyst prepared in Example 2 and the catalyst prepared by the conventional co-precipitation method were evaluated for catalytic performance of methanol oxidation to formaldehyde according to the reaction conditions in Table 5, and the specific evaluation method was the same as that in Example 1. The initial activity and selectivity of the catalyst are shown in Table 5. The loss of Mo component after long-term operation was also evaluated, and the Mo content in the upper catalyst of the reactor before the reaction and after 720 hours of reaction (ICP test) is shown in Table 6.
[0045] Table 5 Catalyst reaction evaluation
[0046]
[0047]
[0048] Table 6 Catalyst element content before and after reaction
[0049] Before reaction After the reaction element Mo content (%) Mo content (%) FeMo-3 38.9554 38.1423 FeMo-PEG-6000 38.9512 38.8859
[0050] As shown in Table 6, the FeMo-PEG-6000 catalyst prepared in Example 2 can still maintain the initial activity and selectivity after 720 hours of reaction, and ICP confirms that the Mo content is not lost during the reaction.
Claims
1. A method for preparing an ultrafine iron-molybdenum catalyst, characterized in that: The method comprises the following steps: Step 1: adding a complexing agent to an aqueous solution of a trivalent iron salt, and then adding an aqueous solution of nitric acid to change the solution from a reddish brown opaque state to a clear state, stirring for 1 to 4 hours to obtain a mother solution; the complexing agent is any one of polyethylene glycol, polyvinyl alcohol, and polyvinyl pyrrolidone; Step 2: adopt an impregnation method to impregnate the mother liquor of step 1 into MoO3 powder, and obtain an ultrafine iron-molybdenum catalyst after roasting; or adopt a co-precipitation method to co-precipitate the mother liquor of step 1 with ammonium molybdate and then roast to obtain an ultrafine iron-molybdenum catalyst; the molybdenum-iron atomic ratio in the iron-molybdenum catalyst is 1:1 to 3:
1.
2. The method for preparing the ultrafine iron-molybdenum catalyst according to claim 1, characterized in that: In step 1, the added mass of the complexing agent is Fe 3+ 0.5 to 3 times the mass.
3. The method for preparing the ultrafine iron-molybdenum catalyst according to claim 1, characterized in that: In step 1, the trivalent iron salt is ferric nitrate or ferric chloride.
4. The method for preparing the ultrafine iron-molybdenum catalyst according to claim 1, characterized in that: In step 1, the concentration of the nitric acid aqueous solution is 1 to 8 mol / L.
5. The method for preparing the ultrafine iron-molybdenum catalyst according to claim 1, characterized in that: In step 2, MoO3 powder is added to the mother liquor of step 1 by impregnation method, stirred for 2 to 6 hours to completely evaporate the water, dried at 80 to 120°C, and calcined at 400 to 500°C for 4 to 16 hours to obtain an ultrafine iron-molybdenum catalyst.
6. The method for preparing the ultrafine iron-molybdenum catalyst according to claim 1, characterized in that: In step 2, a co-precipitation method is adopted to add an aqueous ammonium molybdate solution to the mother liquor of step 1 or to add the aqueous ammonium molybdate solution and the mother liquor of step 1 to a precipitation kettle at the same time, and the pH of the system is controlled at 1.7 to 2.4 by dropping ammonia water, and the iron-molybdenum powder obtained after co-precipitation is calcined at 400 to 500° C. for 4 to 16 hours to obtain an ultrafine iron-molybdenum catalyst.
7. Use of the ultrafine iron-molybdenum catalyst obtained by the preparation method according to any one of claims 1 to 6 in catalyzing the selective oxidation of methanol to produce formaldehyde.
8. Use of the ultrafine iron-molybdenum catalyst according to claim 7 in catalyzing the selective oxidation of methanol to produce formaldehyde, characterized in that: The ultrafine iron-molybdenum catalyst powder is pressed into tablets and then loaded into a fixed bed reactor with an air velocity of 6000 to 13000 h -1 The oxygen content in the inlet air is diluted with nitrogen to a volume concentration of 10% to 20%, and the pump speed is adjusted so that the volume fraction of methanol in the gas phase after gasification is 6% to 10%. The reaction is carried out under normal pressure and the reaction temperature is 280 to 350°C.
Citation Information
Cited By
Iron-molybdenum catalyst and preparation method and application thereof
CN121534726A